Visceral and Vascular Imaging Findings of Hypovolemic Shock in Contrast-enhanced Computed Tomography: A Case Report - Vaishali Bodhraj Dhawan; Rakshanda Pravin Agrawal; Gahana Kataria (Journal of Clinical and Diagnostic Research)
Shock, a medical emergency condition secondary to an underlying cause, requires urgent diagnosis for timely management. Imaging can play an important role in this process. Certain identifiable features on Contrast-enhanced Computed Tomography (CECT) may alert radiologists to the presence of Hypovolemic Shock (HS). A spectrum of visceral and vascular CT signs has been documented to represent the underlying shock condition. Authors, hereby present a case of 78-year-old male patient, depicting visceral and vascular imaging findings of HS, as observed on a CECT of the abdomen and pelvis. The visceral findings included hypoenhancement of the liver and spleen, heterogenous hyperenhancement of the kidneys and adrenal glands and abnormal dilation of small bowel loops. The vascular findings were characterised by the flattening of the Inferior Vena Cava (IVC). The present case report was aimed to help radiologists increase their awareness of the CT signs of HS and assist physicians in taking early measures for adequate management.